Buckling failure of rectangular oil tank with corrugated wall - Mikhail Riyad Mohd Ridzuan (Nanyang Technological University, 2021)
Corrugated walls in oil tankers have numerous advantages that range from exhibiting lower mass, easier tank cleaning operations and lesser corrosive problems. Corrugated walls are commonly used in vessels as they have lateral flexibility and vertical rigidity. These advantages provide the corrugated wall with buckling resistance and flexibility of inward and outward movement. However, these tanks are still subjected to damage and local buckling may happen from over pressuring during loading/unloadingoperations. Deformation or buckling happens instantaneously. In this present case, a sudden inward and outward movement of the corrugated tank due to buckling would cause pulling-in action of the wall and large rotation at the welded joints at the top/bottom edges of the tank and brought about a secondary failure therein. This was primarily caused by over pressuring during loading operations. This project will analyse the corrugated tank and determine the buckling load that caused the deformation. In this project, the corrugated wall of the tank is modelled in Solidworks and then analysed using the Finite Element Analysis (FEA)softwarethrough ANSYS. Only the buckled wall is modelled and the boundary conditions are assumed that the two vertical and bottom edges are fixed. Eigenvalue buckling will be used to predict the pressure needed for the 12 mm wall to buckle. The project will then further analyse the pressure load needed for 13 mm, 14mm and 15 mm thick corrugated wall to buckle. The Eigenvalue buckling analysis evidently showsthe location and pressure needed for the 12 mm corrugated wall to buckle. This has been accurately predicted as compared to the work done by Professor Ong’s analysis. The 13-15 mm analysis was then collated and a relationship was made from it. It showed that, as we move towards a thicker corrugated wall, a higher pressure is needed. The deformation through the 12-15 mm thickness happens at approximately 7 m high from the base of the corrugated wall. It also showed similar signs that buckling happens at the corner of the corrugations where there is high stress concentrations.